Different voices from community groups to support sustainable tourism development at Iranian World Heritage Sites: evidence from Bisotun - Olya, Hossein G. T.; Alipour, Habib; Gavilyan, Yaqub (Routledge Journals, Taylor & Francis Ltd, 2018)
This empirical study investigates the causal factors affecting support for sustainable tourism development (SSTD) at a world heritage site in Bisotun, a city in Kermanshah Province, Iran. It uses social exchange theory to assess the effects of community attachment, community involvement, perceived benefits, and perceived costs on SSTD. Using social identity theory, it identifies whether these associations significantly vary across four different community groups: farmers, businesses, handicraft sellers, and local government employees. A questionnaire was administered to 489 respondents from these four community groups in the Bisotun area. The hypotheses were tested using structural equation modelling and invariance metric tests. The results revealed that community attachment, community involvement, and perceived benefits had a significant and positive impact on SSTD. The results of the metric invariance tests show that the effects of community attachment and community involvement on SSTD varied across the community groups at this world heritage site located in a developing country. The study discusses the theoretical and managerial implications of these findings.
Keywords: World heritage site; community; sustainable development; Bisotun; Iran